Linear Precoder Design for SWIPT-Enabled Relay Networks With Finite-Alphabet Inputs - Chen, Baojun; Zhu, Xiaodong; Tu, Xiaodong; Guo, Yunshan (IEEE access, 2020)
This paper considers the problem of mutual information maximization in a two-hop relay network with simultaneous wireless information and power transfer (SWIPT), where the relay nodes use the power splitting (PS) scheme to harvest the energy for information forwarding. Unlike previous research, this paper focuses on a more practical scenario, where the inputs to the network are assumed to be finite-alphabet signals. Although each node in the network is assumed to have single antenna, we show that the relay network can be regarded as an effective multiple-input multiple-output (MIMO) system. Our goal is to perform the joint optimization on the precoder at source and PS ratio at relays to maximize the mutual information. Although the formulated problem is nondeterministic polynomial-time (NP)-hard, we theoretically analyze the optimal PS ratio; then, by using the structure of optimization problem, a near optimal precoder design based on semidefinite relaxation (SDR) is proposed; further, to reduce the complexity of algorithm, another precoder design based on search technique, which exploiting the structure of precoder, is developed only with a slight performance degradation. Simulation results verify the efficacy of proposed precoder designs.